Student selection process for undergraduate medical programme amid the Covid-19 pandemic: lessons learned and future directions for Universiti Putra Malaysia - Adam, Siti Khadijah; Mohamad, Fadzilah; Maniam, Sandra; Ismail, Siti Irma Fadhilah; Hasan, Mohd Khairi; Mohtarrudin, Norhafizah; Ibrahim, Normala (UPM Press, 2022)
Medical schools worldwide employ a variety of strategies in their student selection process due to the large number of academically qualified applicants and the limited places to offer. The selection process is crucial because the accepted candidates shall be able to complete the medical training and eventually will become safe and competent doctors. Multiple mini-interview (MMI) has increasingly been adopted as the preferred method of medical student selection due to its acceptability, feasibility, reliability and validity (1). In MMI, candidates rotate around a series of stations designed to assess cognitive and non-cognitive attributes in a finite time allotment (2). The Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM) has been conducting MMI since 2017 for selecting undergraduate Doctor of Medicine (MD) students. However, the coronavirus disease 2019 (COVID-19) pandemic has caused many challenges and sudden changes medical schools worldwide, including the admission process. In UPM particularly, the usual face-to-face in-person MMI became infeasible due to the social distancing policies resulting from the pandemic.